University student mental health: a report of extension experience in the pandemic period (Research, Society and Development, 2021)
The research aims to report the experience and impact on the mental health of university students participating in an extension project during the pandemic period. The study was developed from the collection of quantitative and qualitative data through an online form with open and closed questions that invited the participant to analyze their mental health before and during the suspension period from the academic calendar, with the offer of remote activities, due to the health crisis caused by the coronavirus. The results show that there was an important impact on the mental health of most students. During the pandemic, 54.5% of the participants declared that most of the time they considered their mental health to be regular and 36.4% said that most of the time was bad. After participating in the course, 54.5% went on to declare that their mental health was good most of the time, with a drop over those who considered most of the regular time, 27.3%. It is hoped that this experience will corroborate future actions of this nature, aiming at the well-being and health of university students.